Clinical Outcome After Intra‐Articular Administration of Bone Marrow Derived Mesenchymal Stem Cells in 33 Horses With Stifle Injury. Issue 3 (16th January 2014) - Ferris, Dora J.; Frisbie, David D.; Kisiday, John D.; McIlwraith, C. Wayne; Hague, Brent A.; Major, Michael D.; Schneider, Robert K.; Zubrod, Chad J.; Kawcak, Christopher E.; Goodrich, Laurie R.
<x xml:space="preserve">Abstract</x> Objective To report outcome of horses with femorotibial lesions (meniscal, cartilage or ligamentous) treated with surgery and intra‐articular administration of autologous bone marrow derived mesenchymal stem cells (BMSCs). Study Design Prospective case series. Animals Horses (n = 33). Methods Inclusion criteria included horses that had lameness localized to the stifle by diagnostic anesthesia, exploratory stifle arthroscopy and subsequent intra‐articular administration of autologous BMSCs. Case details and follow‐up were gathered from medical records, owner, trainer or veterinarian. Outcome was defined as returned to previous level of work, returned to work, or failed to return to work. Results Follow‐up (mean, 24 months) was obtained; 43% of horses returned to previous level of work, 33% returned to work, and 24% failed to return to work. In horses with meniscal damage (n = 24) a higher percentage in the current study (75%) returned to some level of work compared to those in previous reports (60–63%) that were treated with arthroscopy alone, which resulted in a statistically significant difference between studies (P = .038). Joint flare post injection was reported in 3 horses (9.0%); however, no long‐term effects were noted. Conclusions Intra‐articular administration of BMSC postoperatively for stifle lesions appeared to be safe, with morbidity being similar to that of other biologic agents. Improvement in ability to return to work may be realized with BMSC treatment compared to surgery alone in horses with stifle injury.